Isolation and functional analysis of phage-displayed antibody fragments targeting the staphylococcal superantigen-like proteins - Alanko Ida; Sandberg Rebecca; Brockmann Eeva-Christine; de Haas Carla J. C.; van Strijp Jos A. G.; Lamminmäki Urpo; Salo-Ahen Outi M. H. (Wiley, 2025)
Staphylococcus aureus produces numerous virulence factors that manipulate the immune system, helping the bacteria avoid phagocytosis. In this study, we are investigating three immune evasion molecules called the staphylococcal superantigen-like proteins 1, 5, and 10 (SSL1, SSL5, and SSL10). All three SSLs inhibit vital host immune processes and contribute to S. aureus immune evasion. This study aimed to identify single-chain variable fragment (scFvs) antibodies from synthetic antibody phage libraries, which can recognize either of the three SSLs and could block the interaction between the SSLs and their respective human targets. The antibodies were isolated after three rounds of panning against SSL1, SSL5, and SSL10, and their ability to bind to the SSLs was studied using a time-resolved fluorescence-based immunoassay. We successfully obtained altogether 44 unique clones displaying binding activity to either SSL1, SSL5, or SSL10. The capability of the SSL-recognizing scFvs to inhibit the SSLs' function was tested in an MMP9 enzymatic activity assay, a P-selectin glycoprotein ligand 1 competitive binding assay, and an IgG1-mediated phagocytosis assay. We could show that one scFv was able to inhibit SSL1 and maintain MMP9 activity in a concentration-dependent manner. Finally, the structure of this inhibiting scFv was modeled and used to create putative scFv-SSL1-complex models by protein-protein docking. The complex models were subjected to a 100-ns molecular dynamics simulation to assess the possible binding mode of the antibody.